"Men are for Sex and Women are for Marriage": On the Duality in the Lives of Jewish Religious Gay Men Married to Women. Issue 4 (8th August 2019) - Zack, Eyal; Ben-Ari, Adital
Abstract: The aim of this qualitative study was to examine the lived experience of married Jewish religious men who are also gay. Twenty in-depth interviews were conducted with participants, living in Israel, who defined themselves as orthodox Jews and gay men married to women. Phenomenological analysis revealed 3 key themes: a sense of social obligation to marry a woman; a lived reality characterized by split and duality; and a diverse experience that ranges from feelings of shame and guilt to a sense of acceptance and reconcilement. The findings suggest that although some men struggle to manage a life with a secret same-sex orientation while experiencing frustration and distress, other men find much greater meaning and significance in their sense of family and community belonging than in a life lived according to their sexual orientation. The findings indicate the great importance of religious affiliation and beliefs in shaping the lives of these men. Implications for social and practical interventions are discussed, with special reference to the coming out process and the ethical standpoint of the therapist.